1955
DOI: 10.1111/j.1151-2916.1955.tb14585.x
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibria in the System BaO–TiO2

Abstract: The system BaO-Ti02 was investigated using quenching, strip-furnace, and thermal techniques. Five compounds were found to exist in the system: BazTi04, BaTiOa, BaTizOa, BaTi307, and BaTi409. Of these, only barium metatitanate (BaTi03) melts congruently (at 1618°C.). The dititanate melts incongruently at 1322°C. to yield BaTiOr and liquid ; the trititanate melts at 1357OC. to yield BaTi409 and liquid; the tetratitanate melts to TiOz and liquid at 1428OC. The nature of melting of the orthotitanate could not be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(100 citation statements)
references
References 14 publications
6
87
0
2
Order By: Relevance
“…[1][2][3][4][5] Our group 6,7) and Akishige et al 8) independently synthesized single-crystalline BT 2 and reported the significant ferroelectricity only in the bdirection. Since BT 2 can be easily decomposed into BaTiO 3 (BT) and Ba 6 Ti 17 O 40 (B 6 T 17 ) above 1500 K, large-scale crystalline BT 2 can be hardly prepared.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Our group 6,7) and Akishige et al 8) independently synthesized single-crystalline BT 2 and reported the significant ferroelectricity only in the bdirection. Since BT 2 can be easily decomposed into BaTiO 3 (BT) and Ba 6 Ti 17 O 40 (B 6 T 17 ) above 1500 K, large-scale crystalline BT 2 can be hardly prepared.…”
Section: Introductionmentioning
confidence: 99%
“…This morphology may be attributed to the presence of a liquid phase during sintering 390 , ascribed to the eutectic point that Ba 6 Ti 17 O 40 forms with BT at ~ 1320 °C. [387][388][389] Liquid phase sintering could explain the presence of intragranular porosity in coarse grains, as it was reported that intragranular porosity requires fast mobility of grain boundaries above the pore shrinkage rate. 391 A detailed sintering study would be required to corroborate the aforementioned hypothesis, which is out of the scope of this work.…”
Section: Microstructure Characterizationmentioning
confidence: 99%
“…~450°C in the binary B 2 O 3 -TiO 2 system [Pavlikov et al, 1976]; compositions content 30÷35 mol% BaO around eutectic area e 7 (~31.5 mol% BaO) with m.p. 1317°C in the binary BaO-TiO 2 system [Rase & Roy, 1955;O'Bryan &Thomson, 1974], which include BaTi 2 O 5 composition. Area of glass formation from both these areas moves to eutectic areas e 1 (16,5 mol% BaO) with m.p.…”
Section: Methodsmentioning
confidence: 99%
“…On the DTA curve of the 33.3BaO · 66.67TiO 2 (mol%) glass composition strongly expressed exothermic effect with maximum at 740ºС and endothermic effect with minimum at 1320ºС were observed, which show the crystallization and melting of one crystalline phase (Fig.3 , curve 5). According to [Rase & Roy, 1955] the 33.3BaO · 66.67TiO 2 (mol%) composition is melted incongruently at 1310ºС with melt and BaTiO 3 formation.…”
Section: Dta Study Of the Stoichiometric Glass Compositions In The Bamentioning
confidence: 99%
See 1 more Smart Citation